Slow Flow of Couple Stress Fluid Past a Cylinder Embedded in a Porous Medium: Slip Effect - SARKAR, Priya; MADASU, Krishna Prasad (Engineering Transactions, 2023)
An analytical study for the creeping flow of a couple stress fluid past a cylinder embedded in a porous medium is presented using the slip condition. The uniform flow is considered far away from a cylinder. The boundary conditions used are zero couple stress and tangential slip conditions. The modified Bessel functions represent the stream function (the velocity). The drag exerted on a solid cylinder immersed in a porous medium is derived. The impacts of the couple stress, permeability, and slip parameters on the normalized drag force are presented graphically. The drag forces of well-known exceptional cases are reduced. The drag force is a decreasing function of the permeability and couple stress parameters and an increasing function of the slip parameter.